The Enhanced and Tunable Sustained Release of Pesticides Using Activated Carbon as a Carrier - Yang, Jun (Materials (Basel), 2019)
The sustained release of pesticides improves drug utilization efficiency and reduces their adverse effects. Activated carbon (AC) is an excellent adsorbent and promising soil conditioner. It has a rich, porous structure and thus can store and gradually release drugs. In this study, three AC materials with surface areas ranging from 800–2000 m(2)/g were used and two types of modified activated carbons were prepared, and their capacity as drug carriers was evaluated by using 2,4-Dichlorophenoxyacetic acid sodium (2,4-D sodium) as the model pesticide. The preparations were characterized by scanning electron microscopy, nitrogen physical analysis, and zeta potential. The five preparations showed an enhanced and tunable sustained release of drugs. AC1, with the highest specific surface area, possesses the best drug-loading capacity, reaching 679.18 mg/g, but the lowest drug release rate of 32.31% in 96 h. PDA-AC3 has the lowest specific surface area, showing limited drug-loading ability, 82.94 mg/g, but 100% drug release within 72 h. This study suggests that activated carbon has potent applications in agricultural pest control as an inexpensive, effective, controllable, and safe pesticide carrier.